A Novel Earth‐Abundant W‐WC Heterojunction as Efficient Co‐Catalyst for Enhanced Photocatalytic H2 Evolution. Issue 4 (17th January 2020) - Ma, Baojun; Zhang, Sipeng; Wang, Wei; Feng, Li; Zhang, Ruisheng; Lin, Keying; Li, Dekang; Zhan, Haijuan; Yang, Xu
Abstract: New functional materials are of significance for the industry development of coal and tungsten. Here, we reported a novel earth‐abundant W‐WC heterojunction on CdS as an efficient and cheap co‐catalyst for photocatalytic H2 evolution on CdS under visible light irradiation. The W‐WC is simply synthesized from industrial raw material of coal and ammonium tungstate by a simple one‐step calcination strategy. The photocatalytic activities tests show that W‐WC heterojunction has better co‐catalytic performance than W or WC alone, and the optimal photocatalytic activity of W‐WC/CdS reaches 3314 μmol/h/g, which are17.4 and 2.6 times larger than that of CdS and Pt/CdS alone, respectively. Electrochemical tests demonstrate the WC has large specific capacitance and acts as electron reservoir storing the photo‐excited electron from CdS, whereas W mainly acts as the catalytic center. The heterojunction formed between W and WC is favorable for the electron transferring. The different functions of W and WC along with the heterojunction between W and WC account for the superiority of W‐WC. The design and fabrication strategy of the W‐WC heterojunction co‐catalyst benefits for the industrial development of new material and photocatalysis. Abstract : Photocatalytic H2 Evolution : We reported a novel earth‐abundant W‐WC heterojunction as an efficient and cheap co‐catalyst for photocatalytic H2 evolution on CdS under visible light irradiation. The W‐WC is cheap and simply synthesized from industrial raw material of coal. The co‐catalytic efficiency of W‐WC is 2.6 times of Pt. In the composite co‐catalyst W‐WC, the WC shows the large specific capacitance and stores electrons, and the W mainly acts as the catalytic active center for proton reduction.